Editor's Choice – Effect of Carotid Endarterectomy on 20 Year Incidence of Recorded Dementia: A Randomised Trial. (April 2022) - Halliday, Alison; Sneade, Mary; Björck, Martin; Pendlebury, Sarah T.; Bulbulia, Richard; Parish, Sarah; Llewellyn-Bennett, Rebecca; Pan, Holly; Whiteley, William; Pan, Hongchao; Gottsäter, Anders; ,
Abstract : Objective: Stroke and carotid atherosclerosis are associated with dementia. Carotid endarterectomy (CEA) reduces stroke risk, although its effect on later dementia is uncertain. Participants in the Asymptomatic Carotid Surgery Trial (ACST-1), randomly allocated to immediate vs. deferral of CEA (i.e., no intervention unless or until triggered by ipsilateral transient ischaemic attack or stroke), were followed, to study effects on dementia. Methods: From 1993 to 2003, ACST-1 included 3 120 participants with asymptomatic tight carotid stenosis. All UK and Swedish patients ( n  = 1 601; 796 immediate vs. 805 deferral) were followed with trial records, national electronic health record linkage, and (UK only) by post and telephone. Cumulative incidence and competing risk analyses were used to measure the effects of risk factors and CEA on dementia risk. Intention to treat analyses yielded hazard ratios (HRs; immediate vs. deferral) of dementia. Results: The median follow up was 19.4 years (interquartile range 16.9 – 21.7). Dementia was recorded in 107 immediate CEA patients and 115 allocated delayed surgery; 1 290 patients died (1 091 [538 vs. 536] before any dementia diagnosis). Dementia incidence rose with age and with female sex (men: 8.3% aged < 70 years at trial entry vs. 15.1% aged ≥ 70; women: 15.1% aged < 70 years at trial entry vs. 22.4% aged ≥ 70 years) and was higher in those with pre-existing cerebral infarction (silent or with prior symptoms; 20.2% vs. 13.6%). Dementia risk was similar in both randomised groups: 6.7% vs. 6.6% at 10 years and 14.3% vs. 15.5% at 20 years, respectively. The dementia HR was 0.98 (95% confidence interval [CI] 0.75 – 1.28; p  = .89), with no heterogeneity in the neutral effect of immediate CEA on dementia related to age, carotid stenosis, blood pressure, diabetes, country of residence, or medical treatments at trial entry (heterogeneity values p > .05). Conclusion: CEA was not associated with significant reductions in the long term hazards of dementia, but the CI did not exclude a proportional benefit or hazard of about 25%.